Computer Vision for Continuous Bedside Pharmacological Data Extraction: A Novel Application of Artificial Intelligence for Clinical Data Recording and Biomedical Research - Froese, Logan; Dian, Joshua; Batson, Carleen; Gomez, Alwyn; Sainbhi, Amanjyot Singh; Unger, Bertram; Zeiler, Frederick A. (Frontiers in Big Data, 2021)
Introduction- As real time data processing is integrated with medical care for traumatic brain injury (TBI) patients, there is a requirement for devices to have digital output. However, there are still many devices that fail to have the required hardware to export real time data into an acceptable digital format or in a continuously updating manner. This is particularly the case for many intravenous pumps and older technological systems. Such accurate and digital real time data integration within TBI care and other fields is critical are we move towards digitizing healthcare information and integrating clinical data streams to improve bedside care. We propose to meet this gap in technology by building a system that employs Optical Character Recognition through computer vision, using real time images from a pump monitor to extract the desired real time information. Methods- Using freely available software and readily available technology, we built a script that extracts real time images from a medication pump then processes them using Optical Character Recognition to create digital text from the image. This text was then transferred to an ICM+ real-time monitoring software in parallel with other retrieved physiological data. Results- The prototype that was built works effectively for our device, with source code openly available to interested end-user’s. However, future work is required for a more universal application of such a system. Conclusion- Advances here can improve medical information collection in the clinical environment, eliminating human error with bedside charting, and aid in data integration for biomedical research where many complex data sets can be seamlessly integrated digitally. Our design demonstrates a simple adaptation of current technology to help with this integration.